A Novel Model of Electromechanical Contactors for Predicting Dynamic Characteristics - Gongrun Wang (MDPI AG, 2021)
To ensure the reliability of power supply, a dual power supply structure appears in the power distribution system. Power supply switching is a complex physical process. This paper presents a novel model of electromechanical contactors. This model can simulate the multi-physics process of power switching. This article completes the simulation framework for power switching through contactors for the first time. Among them, the structural topology for contactors is also proposed. On the basis of the novel structure topology, an equivalent magnetic circuit model is established to calculate the relationship between driving force, flux linkage, current, and displacement. Then, a co-simulation model is established between the above equations and Adams to obtain the speed characteristics and flight time of the contactor. Subsequently, through the use of Fluent and its secondary development, a magnetohydrodynamic model is established, and the above-mentioned velocity characteristics are imported into it to analyze the arcing characteristics of the contacts under the conditions of the transverse magnetic field and the insulating grid. The effectiveness of power switching is judged by comparing the flight time of the electromechanical model and the arcing time of the magnetohydrodynamic model. The prototype is manufactured and tested on the basis of simulation. Through experimental waveforms and high-speed photography, the accuracy of the simulation model and the practicability of the contactor are verified.